Autonomic imbalance hypothesis and overtraining syndrome - Lehmann, M.; Forster, C.; Dickhuth, H. H.; Gastmann, U. (Medicine & Science in Sports & Exercise, 1998)
PURPOSE: The parasympathetic, Addison type, overtraining syndrome represents the dominant modern type of this syndrome. Beside additional mechanisms, an autonomic or neuroendocrine imbalance is hypothesized as underlying. METHODS/RESULTS: Several findings support this thesis. During heavy endurance training or overreaching periods, the majority of findings give evidence of a reduced adrenal responsiveness to ACTH. This is compensated by an increased pituitary ACTH release. In an early stage of the overtraining syndrome, despite increased pituitary ACTH release, the decreased adrenal responsiveness is no longer compensated. The cortisol response decreases. In an advanced stage of overtraining syndrome, the pituitary ACTH release also decreases. In this stage, there is additionally evidence for decreased intrinsic sympathetic activity and sensitivity of target organs to catecholamines. This is indicated by decreased catecholamine excretion during night rest, decreased beta-adrenoreceptor density, decreased beta-adrenoreceptor-mediated responses, and increased resting plasma norepinephrine levels and responses to exercise. However, this complete pattern is only observed subsequent to high-volume endurance overtraining at high caloric demands. CONCLUSION: The described functional alterations of pituitary-adrenal axis and sympathetic system can explain persistent performance incompetence in affected athletes.